Low bone mineral density among HIV-infected patients in Brazil - Chaba, Daniela Cardeal da Silva (2017)
Decrease in bone mineral density (BMD) has been a complication among people living with HIV/AIDS. To investigate the prevalence of osteopenia/osteoporosis among HIV-infected people living in São Paulo city, we studied 108 HIV-infected patients (79 men and 29 women). We extracted data from patients’ medical records and BMD was measured by dual-energy X-ray absorptiometry (DXA). Median age of participants was 42 years (interquartile range [IQR] 36-48 years), and the median time since HIV diagnosis was 4.01 years (IQR 2-11 years). Patients had acquired HIV primarily by the sexual route (men who have sex with men 44%, heterosexual 49%). Median age, duration of HIV infection, duration of ART and CD4 nadir were similar for men and women. Plasma viral load was undetectable for 53 patients (49%). Median CD4 T cell count was 399 cells/µL (IQR 247 - 568). Twenty five patients (23%) had LBMD, and there was no statistically significant difference between men and women (